PSYCHOLOGICAL AND PEDAGOGICAL BASES OF THE SYSTEM OF CRITERIA EVALUATION ACCORDING TO THE SUBJECT GEOGRAPHY - Калкашев, С.; Абдиманапов, Б.; Усенов, Нурбол; Гордеева, Зинаида (Pedagogy and Psychology, 2022)
This article analyzes the programs of education reform and considers the need to introduce criteria-based assessment in the education system. The updated educational program also reflects the goals and objectives of long-term, medium-term, and short-term planning, as well as its own characteristics. The skills required by the student in accordance with the standard and the competence of the teacher of the XXI century in the formation of these skills were discussed. The general idea of all types, concept and order, characteristics of the assessment is given. What should be taken into account based on the criteria assessment? questions about how to implement it are covered with concrete examples and scientific evidence. The content of the criteria-based assessment system is presented in a diagram, and the standards, tools, process, and results of the assessment are described in detail. New ideas were considered, the content and methodology of formative and summative assessment were revealed. The pedagogical and psychological aspects of the formation of competencies are investigated and justified. These aspects determined the important formulation of the assessment and formed the subject skills and values of criteria-based assessment.